Mangrove Forest Development Strategy in Muara Tourism Village, Teluk Naga District, Tangerang, Indonesia - Saputri, Deby Aini; Wahyudi, Uud; Khan, Alexander M.A (Yayasan Ilomata, 2024)
One kind of ecotourism makes use of the resources already present in a destination's natural and cultural landscapes. Muara Village in Tangerang Regency is home to a mangrove forest that could be transformed into an ecotourism hotspot. The purpose of this study is to investigate the feasibility of creating an ecotourism destination in Muara Village's mangrove forest, as well as the obstacles that may be in the way, and to provide solutions. The study used a descriptive qualitative approach, gathering data via in-depth interviews, literature reviews, and field observations. Mangrove woods in Muara Village have enormous untapped potential in terms of biodiversity and educational value, according to the study. The main challenges faced are the lack of public awareness about the importance of preserving mangrove forests and the limited tourism support facilities. The proposed ecotourism development strategy includes increasing the capacity of local communities, developing supporting infrastructure, and sustainable promotion.